Extraction and characterization of wax from sugarcane bagasse and the enzymatic hydrolysis of dewaxed sugarcane bagasse. Issue 3 (16th March 2017) - Qi, Gaoxiang; Peng, Fen; Xiong, Lian; Lin, Xiaoqing; Huang, Chao; Li, Hailong; Chen, Xuefang; Chen, Xinde
ABSTRACT: Extraction of high-value products from agricultural wastes is an important component for sustainable bioeconomy development. In this study, wax extraction from sugarcane bagasse was performed and the beneficial effect of dewaxing pretreatment on the enzymatic hydrolysis was investigated. About 1.2% (w/w) of crude sugarcane wax was obtained from the sugarcane bagasse using the mixture of petroleum ether and ethanol (mass ratio of 1:1) as the extraction agent. Results of Fourier-transform infrared characterization and gas chromatography–mass spectrometry qualitative analysis showed that the crude sugarcane wax consisted of fatty fractions (fatty acids, fatty aldehydes, hydrocarbons, and esters) and small amount of lignin derivatives. In addition, the effect of dewaxing pretreatment on the enzymatic hydrolysis of sugarcane bagasse was also investigated. The digestibilities of cellulose and xylan in dewaxed sugarcane bagasse were 18.7 and 10.3%, respectively, compared with those of 13.1 and 8.9% obtained from native sugarcane bagasse. The dewaxed sugarcane bagasse became more accessible to enzyme due to the disruption of the outermost layer of the waxy materials.